PERSEPSI DAN IMPLEMENTASI KURIKULUM MERDEKA BELAJAR KAMPUS MERDEKA DI PROGRAM STUDI PGMI DAN IAT IAIN KEDIRI - Rofiah, Tutik Dinur; Fartika Ifriqia; Adifa Ramadea (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
MBKM is the latest curriculum created by the Minister of Education. This curriculum is one of the reforms carried out by making adjustments to the challenges in the era of society 5.0. The aim of this research is to examine perceptions, implementation and obstacles to implementing the MBKM curriculum that occur in the PGMI and IAT IAIN Kediri study programs. The research method used in this research is using a qualitative method with a case study approach. The data collection techniques used were interviews, observation and documentation. The validity of the data used is by triangulating the data sources and cross-checking the data. The data analysis used is data reduction, data presentation, conclusions. The results of this research showed that there were differences at the perception stage between PGMI Study Program who had a scientific background in education and IAT Study Program who had a thought background. There were differences in the registration process, attitudes towards processing and understanding new information as well as interpretations of responding to new information. There were differences. MBKM curriculum implementation pattern in PGMI Study Program and IAT Study Program. There are obstacles in these two study programs that hinder the implementation of the MBKM curriculum, namely starting from funding, partners, and the absence of standard technical guidelines from the institution. The conclusion of this research is that the perception that a person has, be it study program managers, lecturers and students, can influence the implementation of the MBKM curriculum in both the PGMI Study Program and IAT IAIN Kediri.